Adaptation of the Work Fatigue Symptoms Questionnaire: A Proposal - Vega-Valero, Cynthia Zaira (Universidad Autónoma de Tamaulipas, 2019)
An adaptation of the Work Fatigue Symptoms Questionnaire (WFSQ) with a different response format is presented, in order to make it amenable for comparison with other measures. Participants were volunteer adults who, at the moment of the interview, were working in an organization. Changes in the Questionnaire were made with respect of the response format (form a dichotomous to a polytomous structure). Results show that there was a good scale adjustment to the theoretical proposed factorial structure. However, seven items were eliminated, remaining twenty-three items divided in 3 subscales. The first factor was denominated Work Fatigue General Symptoms (9 items), the second factor was named as Psychical Fatigue (7 items) and the third factor was denominated as Psychological Components of Work Fatigue. In terms of internal consistency, the scale Cronbach’s Alpha indicators show adequate levels. Conclusions stress the necessity of verifying the adequacy of this scale, to be achieved through more empirical studies.